Factors associated with health‐related quality of life in patients with cirrhosis: a systematic review. (2nd November 2020) - Rabiee, Anahita; Ximenes, Rafael O.; Nikayin, Sina; Hickner, Andy; Juthani, Prerak; Rosen, Robert H.; Garcia‐Tsao, Guadalupe
Abstract: Background: Patients with cirrhosis have a poor health‐related quality of life (HRQoL). Recognizing factors that affect HRQoL is key in delivering patient‐centred care. Aim: To identify factors most commonly associated with a poor HRQoL in adults with cirrhosis in a systematic review of the literature. Methods: Four databases (MEDLINE, EMBASE, CENTRAL and PsycINFO) were searched from inception to March 2020, using terms related to patient‐reported outcomes plus cirrhosis. Studies that analysed an association between at least one factor and HRQoL in adult patients with cirrhosis were included. Abstract and full‐text screening was performed by two reviewers. Data were collected on factors evaluated in each study and the significance of their association with HRQoL. Results: A total of 10647 citations were reviewed, of which 109 met eligibility criteria. 76% of the studies used a generic instrument while only 45% used liver‐specific instruments. Among identified factors, demographic factors and cirrhosis aetiology were not generally associated with poor HRQoL except for poor social support. Depression, poor sleep and muscle cramps affected HRQoL in all the studies that evaluated them. Among comorbidities, frailty, falls, malnutrition and cognitive impairment were also associated with poor HRQoL in the majority of studies. Among cirrhosis‐specific decompensating events, only hepatic encephalopathy (HE) was consistently associated with impairment in HRQoL (75% of studies). Conclusion: Many factors impact poor HRQoL in patients with cirrhosis such as depression, muscle cramps, poor sleep, falls, frailty and malnutrition. Among cirrhosis decompensating events, HE was the complication most commonly associated with a poor HRQoL.